Development of polyresistance in microorganisms during antibiotic therapy in a multidisciplinary hospital during a pandemic COVID-19 - Nikolay B. Esaulenko; Olga V. Tkachenko; Sergey P. Kazakov; Denis V. Davydov; Andrey A. Zaytsev; Sergey A. Chernov (ZAO "Consilium Medicum", 2024)
Background. Irrational and excessive use of antimicrobials drugs (AMD) creates conditions for the development of a global crisis of health systems around the world associated with antibiotic resistance. Aim. To conduct a retrospective study of the impact of the use of AMD on the change in the microbiological landscape and the sensitivity of microorganisms in the conditions of pandemic of the new coronavirus infection (COVID-19) in 2020-2021 in intensive care departments (ICD) of a multidisciplinary hospital. Materials and methods. In the course of the work, strains of microorganisms isolated from patients and from the surfaces of the hospital environment and changes in their sensitivity to significant groups of AMD in ICD for somatic and infectious patients with COVID-19 were compared. The sensitivity of the isolates was evaluated in accordance with the criteria of requirements of European Committee on Antimicrobial Susceptibility Testing - EUCAST, version 10.0, 2020. Results. A total of 1,394 isolates were studied, including 1,379 clinical and 15 isolates from the surfaces of the hospital environment. It was found that in all ICD in 2020-2021, gram-negative microorganisms prevailed in infectious loci in 70% of cases or more. In 2021, in the ICD in infectious patients with COVID-19, the persistent dominance of the Acinetobacter baumannii microorganism was revealed with an increase in the number of poly- and pan-resistant strains - 48.7%. While in the ICD for somatic patients Klebsiella Pneumoniae prevailed among gram-negative microorganisms - 37.5% in 2020 and 43.7% in 2021. It has been shown that in one department or in adjacent departments of the same medical institution, various nosocomial microorganisms with an unequal set of resistance genes and sensitivity to AMD may appear over time. Conclusion. The necessity of conducting constant microbiological monitoring and a passport of the medical department with mandatory registration of not only isolated strains of microorganisms, but also resistance genes in order to optimize the appointment of timely adequate empirical antimicrobial therapy is substantiated. The period of the latter should be as short as possible, and confirmed by convincing clinical signs of bacterial infection, and subsequently by the isolation of nosocomial flora from the biomaterial of critical loci from patients.